Takhrij and Syarah Hadith of Agrotechnology The Study of Farming - Muhammad Subhan Sabiq; Wahyudin Darmalaksana; Husnul Qodim; Sofiya Hasani (Gunung Djati Conference Series, 2021)
This study aims to discuss the hadith with regard to agrotechnology. This research method is a qualitative type through literature and field studies with the takhrij and sharah hadith approaches. Results and discussion of this study Farming is an activity that has many benefits. Such as land use, providing jobs, practicing patience and tawakkal and many others. Farming is also recommended in Islam as mentioned in the hadith of the Prophet Muhammad.